2011
DOI: 10.1007/s00244-011-9714-7
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Mercury Allocation into Egg Components is Independent of Dietary Exposure in Gentoo Penguins

Abstract: Avian eggs have become one of the most common means of evaluating mercury contamination in aquatic and marine environments and can serve as reliable indicators of dietary mercury exposure. We investigated patterns of mercury deposition into the major components of penguin eggs (shell, membrane, albumen, and yolk) using the Gentoo penguin (Pygoscelis papua) as a model species. Eggs were collected from both wild and captive populations of Gentoo penguins to compare the allocation of mercury into individual egg c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 23 publications
3
30
0
Order By: Relevance
“…Eggshells were cleaned of organic debris in the field and stored in individually labeled plastic bags until preparation for mercury and stable isotope analysis. While eggshell membrane can reliably document mercury exposure in female birds in the absence of other tissues (Morera et al 1997;Akearok et al 2010;Brasso et al 2012b), the timing of egg formation must be considered when interpreting these data. As migratory species, mercury concentrations in egg tissues in Adélie and Chinstrap penguins are reflective of late-winter, prebreeding dietary exposure to mercury away from the breeding colony.…”
Section: Sample Collectionmentioning
confidence: 98%
See 1 more Smart Citation
“…Eggshells were cleaned of organic debris in the field and stored in individually labeled plastic bags until preparation for mercury and stable isotope analysis. While eggshell membrane can reliably document mercury exposure in female birds in the absence of other tissues (Morera et al 1997;Akearok et al 2010;Brasso et al 2012b), the timing of egg formation must be considered when interpreting these data. As migratory species, mercury concentrations in egg tissues in Adélie and Chinstrap penguins are reflective of late-winter, prebreeding dietary exposure to mercury away from the breeding colony.…”
Section: Sample Collectionmentioning
confidence: 98%
“…Mercury concentrations in feathers of adult Pygoscelis penguins averaged \0.50 ppm, fw; the highest mercury concentration was 2.39 ppm (Gentoo penguin). Using relationships described by Brasso et al (2012b), eggshell membrane mercury concentrations were found to be associated with whole egg mercury concentrations within the background (low) risk category for potential adverse effects of maternally deposited mercury (Evers et al 2003). Chicks with down mercury concentrations \13.0 ppm, fw have been suggested to be at minimal risk of adverse impacts of maternally deposited mercury into the egg (Ackerman and Eagles-Smith 2009); average mercury concentrations in chick down in the present study were \0.30 ppm, fw.…”
Section: Temporal Limitations and Toxicity Thresholdsmentioning
confidence: 98%
“…It is, therefore, needful to rely on the available information in the literature to predict Hg distribution in the different components of the egg of avian species. One of such studies is that recently reported for Gentoo penguins where up to 92.0% of the total Hg in their eggs were allocated to the albumen, 6.7% in the yolk, 0.4% in the membrane and 0.9% in the eggshell (Brasso et al, 2012).…”
Section: Assessing Ecological Risks Associated With Hg Levels In Invementioning
confidence: 99%
“…Because the eggs have a consistent structure and composition, their mercury levels potentially reflect the status of mercury exposure in the females. Egg laying, therefore, may provide an important mechanism for eliminating methylmercury from the body of female birds [7,15]. Methylmercury is the primary form of mercury in eggs [14] and is deposited into various egg components including albumen, yolk, shell, and membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Egg sampling is relatively easy and minimally invasive to the population and is used widely in studies of avian toxicology [13]. Because egg mercury levels are correlated with mercury concentration in the blood of female birds, and mercury concentrations in different egg components are mutually correlated, whole eggs are believed to provide reliable information on recent mercury exposure [5,7,15,16]. Egg laying, therefore, may provide an important mechanism for eliminating methylmercury from the body of female birds [7,15].…”
Section: Introductionmentioning
confidence: 99%